3.26
-1.5х=1.2-6.09
-1.5х=-4.89
х=-4.89:(-1.5)
х=3.26
1)
2(3x + 1) - x ≤ 3(x + 4)
6х + 2 - х ≤ 3х+12
5х + 2 ≤ 3х + 12
5х - 3х ≤ 12 -2
2х ≤ 10
х ≤5,
2)
7x + 4(x - 2) > 6(1 + 3x)
7х + 4х - 8 > 6 + 18x
11x - 8 > 6 + 18x
11x - 18x > 6 + 8
-7x > 14
x < - 2
3)
2(x - 1) - 3(x + 2) < 6(1 + x)
2x - 2 - 3x - 6 < 6 + 6x
-x - 8 < 6 + 6x
-x - 6x < 6 + 8
-7x < 14
x > -2
4)
7(y + 3) - 2(y + 2) ≥ 2(5y + 1)
7y + 21 - 2y - 4 ≥ 10y + 2
5y + 17 ≥ 10y + 2
5y - 10y ≥ 2 - 17
-5y ≥ -15
y ≤ 3
Пошаговое объяснение:
Пошаговое объяснение:
-1,5х=1,2-6,09
-1,5х=-4,89
Х=-4,89:(-1,5)
Х=3,26